Toilet mastectomy as a possible and recommended solution to improve the quality of life of advanced breast cancer patients – case series - Radziszewski, Marcin; Choromańska, Ewa; Nowak, Adriana; Kowalewski, Radosław; Radziszewski, Jakub (Medycyna Paliatywna/Palliative Medicine, 2021)
The five-year survival rate among breast cancer patients in Poland between 2010 and 2014 was 76.5%. It is approximately 10% lower than in Western Europe (United Kingdom 85.6%, Austria 84.8%, Germany 86%). The reason for this situation is complex. One of the factors is the fact that patients seek medical advice in very advanced stages of cancer, often requiring toilet mastectomy. We present the surgical treatment of five female advanced locoregional breast cancer patients admitted to the General, Vascular, and Oncological Surgery Department of the Multidisciplinary Hospital Warsaw–Międzylesie between 2017 and 2020. Two patients were treated with toilet mastectomy with skin flap transposition while three of them underwent a simple toilet mastectomy. We present the technical aspects of flap sliding to cover large skin defects after palliative breast resection. According to our observation the quality of life among these patients improved significantly, however, we have no evidence of extension of the length of life. In the most advanced breast cancer patients, toilet mastectomy is suitable even if this procedure requires skin flap transposition. We assess it as a recommended surgical treatment to improve the life quality of such patients, however, further research is required.